RETRACTED: Assessment of the distance learning server's operation strategies and service capacity in advance - Abdullaev Eldor; Zakirov Vakhid; Shukurov Farrukh (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001